Cytotoxic Activity, Cell Cycle Inhibition, and Apoptosis-Inducing Potential of Athyrium hohenackerianum (Lady Fern) with Its Phytochemical Profiling. (2nd June 2022) - Elasbali, Abdelbaset Mohamed; Al-Soud, Waleed Abu; Al-Oanzi, Ziad H.; Qanash, Husam; Alharbi, Bandar; Binsaleh, Naif K.; Alreshidi, Mousa; Patel, Mitesh; Adnan, Mohd
Abstract : In the present study, we investigated the cytotoxic effects of Athyrium hohenackerianum ethanolic extract (AHEE) on the proliferation of breast, lung, and colon cancer cells. The AHEE was tested for its effect on the progression of the cell cycle, followed by induction of apoptosis determination by flow cytometry. Real-time qRT-PCR was also utilized to observe the initiation of apoptosis. In addition, GC-MS was performed in order to identify the active phytochemicals present in the AHEE. A cytotoxic activity with an IC50 value of 123.90  μ g/mL against HCT-116 colon cancer cells was exhibited by AHEE. Following propidium iodide staining, annexin-V/PI, and clonogenic assays, AHEE treatment results in cell arrest in the S phase, causing an increase in the early and late phases of apoptosis and displaying antiproliferative potential, respectively. The morphological alterations were further monitored using acridine orange/ethidium bromide (AO/EB) staining. When compared with the control cells, features of apoptotic cell death, including nuclear fragmentation, in the AHEE- treated cells were noticed. The apoptosis was also confirmed by detecting the increased expression of p53 and caspase-3 along with the downregulation of Bcl-2 . GC-MS analysis revealed that trans-linalool oxide, loliolide, phytol, 4, 8, 12, 16-tetramethylheptadecan-4-olide, and gamma-sitosterol were the major phytochemical constituents. Based on these findings, it can be suggested that AHEE causes cellular death via apoptosis, which should be further explored for the identification of active compounds responsible for these observed effects. Therefore, AHEE can be used in the pharmaceutical development of anticancer agents for cancer therapeutics.